Systematic Literature Review: Pengaruh Pola Makan Kariogenik pada Anak Sekolah Terhadap Status Kesehatan Gigi dan Mulut - Priandini, Aulia; Larasati, Ratih; Hadi, Sunomo; Prasetyowati, Silvia (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
The maintenance of dental health in school-aged children is crucial as their dental condition will impact their oral health in adulthood. Consumption habits of cariogenic foods such as sugar can increase the risk of dental caries. Therefore, regulating dietary patterns to avoid excessive sugar consumption is important in reducing this risk. The aim of this study is to elucidate the cariogenic dietary patterns in school children concerning the status of dental and oral health through article reviews. The research strategy employed was a literature review obtained from academic databases including Google Scholar, ProQuest, and Science Direct, focusing on publications within the last 5 years. Keywords used were